Blaming the Victim of Acquaintance Rape: Individual, Situational, and Sociocultural Factors - Gravelin, Claire R.; Biernat, Monica; Bucher, Caroline E. (Frontiers in Psychology, 2019)
Victims of rape are uniquely vulnerable for being blamed for their assault relative to victims of other interpersonal crimes, and thus much research has been conducted to understand why this is the case. But the study of victim blaming in acquaintance rape cases is hindered by contradictory empirical results. Early investigations in victim blaming often treated acquaintance rapes and stranger rapes as synonymous, and thus much of these data are suspect for drawing conclusions particular to acquaintance rape. This paper provides a comprehensive review of the research literature on victim blame in acquaintance rape cases, highlighting inconsistencies, and drawing particular attention to areas of research in need of further exploration. Specifically, we review the commonly studied individual (perceiver) factors that influence victim blaming, as well as common situational (target) factors included or manipulated within sexual assault scenarios. Our review reveals many inconsistent findings and interactions between perceiver and scenario factors. In an effort to make sense of these complex interactions and inconsistent findings, we suggest a need for more transparency in describing the scenarios used in research on victim blaming in sexual assault cases, and greater empirical attention to sociocultural factors that may influence blaming tendencies.